Le Freak an upside down story of family, disco, and destiny - Rodgers, Nile 1952- (Spiegel & Grau, 2011)
Today's pop music--genre-crossing, gender-bending, racially mixed, visually stylish, and dominated by dance music with global appeal--is the world that Nile Rodgers created. In the 1970s and 1980s, he wrote and produced the songs that defined that era and everything that came after. Aside from his own band, Chic, he worked with everyone from Diana Ross and Madonna to David Bowie and Duran Duran, transforming their music and redefining what a pop song could be. But before he reinvented pop music, Nile Rodgers invented himself. Born into a mixed-race, bicoastal family of dope-fiend bohemians, he was on his own by age 16, half-hippie and half-Black Panther. He jammed with Jimi Hendrix, toured with Big Bird, and played in the legendary Apollo Theater house band. And then he discovered disco... Here he gives us the behind-the-scenes tales of the songs we all know, and lovingly re-creates the outsider subcultures that live on in the world of pop he helped to set in motion.--From publisher description